2014
DOI: 10.1016/j.ibusrev.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers through backward linkages and the export performance of business services. Evidence from a sample of Italian firms

Abstract: We provide evidence on the role of spillovers through vertical linkages in service firms' internationalisation process. We combine input-output coefficients with region-level information on downstream manufacturing sector exports to build a measure of spillovers through backward linkages, which we assess as a systematic determinant of Italian BS firms' export status. Once considered firm and sector specificities, export spillovers especially matter for exporting to high-income economies outside Europe. This fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 78 publications
1
7
0
2
Order By: Relevance
“…Services that are being exported and can also be delivered digitally include accounting, auditing and book-keeping services, software related activities, research and design, advertising, travel services, arts, and entertainment, financial and investment services and more. Given the specific characteristics of services when compared to goods, more research is required that investigates the determinants of export performance of service firms (Conti et al, 2014, Pla-Barber and Ghauri, 2012, Sousa et al, 2008, Jaklič et al, 2012. The use of ICT is one such determinant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Services that are being exported and can also be delivered digitally include accounting, auditing and book-keeping services, software related activities, research and design, advertising, travel services, arts, and entertainment, financial and investment services and more. Given the specific characteristics of services when compared to goods, more research is required that investigates the determinants of export performance of service firms (Conti et al, 2014, Pla-Barber and Ghauri, 2012, Sousa et al, 2008, Jaklič et al, 2012. The use of ICT is one such determinant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, most of the previous studies that tested ELGH have concentrated on examining the exports-economic growth relationship at aggregate level while few studies deepen the analysis by disaggregating exports into primary, manufactured and services exports. Presently services have become a tradable component in the global trade hence traditional view 1 on services is no longer valid [10] [11] [12] [13] [14]. The classical economic thought was that services are driven by domestic demand hence the expansion of services beyond the limit causes the detritions of prices [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, it is hard to measure firms' export performance precisely since numerous possible factors influence it, such as spillover effect, industrial linkage effect, and global supply chain. Conti, Turco, and Maggioni [27] examine spillovers' role through backward linkages in Italian firms' export performance. The research found that joining networks with internationalized customers may play an essential role in enhancing firms' exports.…”
Section: Resultsmentioning
confidence: 99%